HUMAN RESOURCE MANAGEMENT INFORMATION SYSTEM GOVERNANCE AT MIS RAUDLATUL MUNAWWARAH TO IMPROVE THE PERFORMANCE AND QUALITY OF EDUCATORS - Murtafiah, Nurul Hidayati (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2024)
Governance of the human resource management information system (SIM SDM) at Madrasah Ibtidaiyah (MI) is an important process that involves managing information and procedures related to human resources efficiently and effectively. HR SIM in madrasas aims to improve institutional performance through employee data management, recruitment, performance assessment, professional development, and other related aspects. The research conducted focused on the governance of Management Information System Implementation at MIS Raudlatul Munawwarah in an effort to improve the performance and quality of teaching staff. The method used is a descriptive qualitative method by analyzing the processes running at MIS Raudlatul Munawwarah. In designing a website-based HR Information System, it is structured based on the Enterprise Architecture Planning (EAP) model. The results of the research carried out are that managing an effective HR Management Information System at Madrasah Ibtidaiyah requires commitment from all stakeholders, including madrasah heads, teachers, administrative staff and other supporting staff. The successful implementation of this system not only increases operational efficiency, but also makes a positive contribution to teacher professional development and improving the quality of education in madrasas.